Fungi Infection in Surgical Department. Systemic and Local Antifungal Therapy - L. A. Blatun; G. E. Skladan; R. P. Terekhova; S. A. Prudnikova; M. G. Krutikov; O. I. Andreytseva; M. N. Yan; A. A. Nikitin; A. A. Ushakov; N. G. Askerov; V. A. Mitish; Yu. S. Paskhalova; et al. (Антибиотики и Химиотерапия, 2020)
Goal. To determine the frequency of detection of pathogenic fungi in a variety of surgical departments, to track the effectiveness of the developed algorithm of systemic and local antifungal therapy. Material and methods. Strains of fungi have been investigated, extracted from the patients situated in the intensive care unit, in the department of thermal injuries, the department of purulent surgery, thoracic, abdominal and vascular surgery. Bioassay Research (biopsy of wounds, bronchial lavage, liquid punctate structures, discharge from catheters and probes, blood culture) was conducted by microscopic and bacteriological methods. Systemic antifungal therapy was strictly prescribed in accordance with the revealed sensitivity of fungi to modern antifungal agents. Local treatment of fungal infestation was carried out with preparations having a wide spectrum of action, including antifungal activity. Results. The species composition of fungi was analyzed in various groups of patients with surgical pathologies. The increase in pathogenic fungi (Candida glabrata and Candida krusei, Candida parapsilosis, Aspergillus ssp.) in the various clinical groups was most often associated with a significant increase in the number of patients with a long course of the infectious process (recurrent cholangitis, peritonitis, pancreatitis, sternomediastinitis, empyema of the pleura, diabetic foot syndrome, extensive trophic ulcers, paraprotein infections, etc). Variconazole, anidulofungin, mycophengin, caspofungin were administered as starting therapy in the study. Drugs that have iodine compounds in their composition (yodopiron 1% solution, Braunodin B. Braun) show high clinical activity in the topical treatment of various lesions of fungal infection, whereas in the case of large amounts of pus in the wound the drug of choice may be Stellanin-PEG 3% ointment. It is advisable to use a solution of 0.01% miramistin for rehabilitation of the tracheobronchial area during diagnostic and therapeutic bronchoscopy, as well as for rinsing the bladder. Conclusion. The problem of fungal infestation is relevant to all clinical departments of a surgical hospital. For successful prevention and treatment of fungal infestation it is necessary not only to carry out regular bacteriological monitoring of the composition of fungi species, but also to determine the sensitivity of isolated strains to current antifungal drugs. The use of drugs for the topical treatment of fungi can significantly reduce the duration of the use of systemic drugs that have a significant economic value.